The Study of Living Sunnah: Theory and Application - Firdaus, Nehna Puteri; Hudaya, Hairul (The Future of Education Journal, 2026)
Contemporary hadith studies demonstrate a shift from purely textual approaches toward contextual understandings that view the Prophet Muhammad’s Sunnah as a living tradition within Muslim social practices. One of the emerging approaches is the study of living sunnah or living hadith, which considers the Sunnah not only as a normative text but also as religious traditions, behaviors, and practices continuously observed by Muslim communities. This article aims to examine the theoretical concept of living sunnah and to explain its applications in Muslim society, particularly in the Indonesian context. This study employs a qualitative approach through library research with a descriptive-analytical design, using primary and secondary literature related to living hadith studies. Data were collected through documentation techniques and analyzed using content analysis with descriptive and interpretative methods. The findings reveal that living sunnah is manifested in three main models: written traditions, oral traditions, and practical traditions. These models are reflected in various religious practices such as aqiqah, tahlilan, qunut in the dawn prayer, dhikr, and the tradition of hadith recitation in Islamic boarding schools. This study concludes that living sunnah demonstrates the dynamic and adaptive nature of hadith, allowing the Prophet’s teachings to remain relevant within diverse socio-cultural contexts without losing their essential Islamic values.